The association between cerebral amyloid angiopathy and intracerebral haemorrhage: systematic review and meta-analysis. Issue 3 (5th November 2011) - Samarasekera, Neshika; Smith, Colin; Al-Shahi Salman, Rustam
Abstract : Background: The aim of this study was to determine the strength of the association between intracerebral haemorrhage (ICH) and cerebral amyloid angiopathy (CAA) in a systematic review of published neuropathological studies. Methods: In April 2011, Ovid Medline (from 1950) and Embase (from 1980) were searched for neuropathological studies that quantified the prevalence of CAA in patients with ICH and in a control group without ICH. Two authors extracted data from each study and meta-analysed their results using a random effects model. Results: 10 neuropathological cross sectional or case control studies were identified, involving 481 cases with ICH and 3219 controls. There was no association between CAA and ICH in any location (OR 1.21, 95% CI 0.87 to 1.68; 10 studies, I 2 29%), deep ICH (OR 0.81, 95% CI 0.30 to 2.19; five studies, I 2 58%) or cerebellar ICH (OR 2.05, 95% CI 0.55 to 7.63; four studies, I 2 0%). CAA was significantly associated with lobar ICH, both overall (OR 2.21, 95% CI 1.09 to 4.45; six studies, I 2 40%) and in the three studies where average ages for cases and controls were comparable (OR 3.24, 95% CI 1.02 to 10.26). Conclusions: There is an association between CAA and lobar ICH, although the association might be stronger if potential confounding factors, distinctive clinical and imaging features of ICH due to CAA and CAA neuropathological severity are taken into account.